PENGARUH PENGUNGKAPAN LINGKUNGAN DAN SOSIAL TERHADAP KINERJA KEUANGAN DENGAN MODERASI BOARD GENDER DIVERSITY - Juanika Fanisa, (2023)
This study aims to determine the effect of environmental and social disclosure on financial performance with board gender diversity as a moderation. The population in this study are non-financial companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The samples obtained in this study amounted to 171 of 57 financial companies selected using purposive sampling. Financial performance is measured by Tobin's Q, environmental and social disclosure is measured by the disclosure index based on the GRI Standard, and board gender diversity is measured by the number of female commissioners divided by the number of commissioners. Hypothesis testing using the STATA 16 application with a significance level of 5% shows that environmental and social disclosures do not affect financial performance and the gender diversity board cannot moderate the relationship of environmental and social disclosures on financial performance.